Spectrophotometric Determination of Ni(II) with Isovanillin Thiosemicarbazone - Lokhande, R.S.; N. Pawar, Rashmi; R. Sharma, Manoj (Asian Journal of Chemistry, 2016)
A new spectrophotometric method using isovanillin thiosemicarbazone (IVTSC) is proposed for the determination of Ni(II) at microgram level. IVTSC reacts with Ni(II) at pH 9 to form a yellow coloured complex which was extracted in n-butanol which shows maximum absorption at 400 nm. The molar absorptivity and Sandell's sensitivity were calculated to be 6.4060 × 103 L mol–1 cm–1 and 0.000109 μg cm–2 respectively. The stoichiometry of the complex was found to be 1 : 2.